2014
DOI: 10.1603/me14064
|View full text |Cite
|
Sign up to set email alerts
|

Natural Vertical Transmission of Ndumu Virus inCulex pipiens(Diptera: Culicidae) Mosquitoes Collected as Larvae

Abstract: Ndumu virus (NDUV) is a member of the family Togaviridae and genus Alphavirus. In Kenya, the virus has been isolated from a range of mosquito species but has not been associated with human or animal morbidity. Little is know about the transmission dynamics or vertebrate reservoirs of this virus. NDUV was isolated from two pools of female Culex pipiens mosquitoes, IJR37 (n = 18) and IJR73 (n = 3), which were collected as larvae on 15 April 2013 from two dambos near the village of Marey, Ijara District, Garissa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…sudanensis and Ao. furfurea also supports existing evidence that it is maintained in nature by transovarial transmission ( Lutomiah et al 2014b ). NDUV was first isolated in South Africa in 1959, and antibodies to the virus have been detected in humans ( Kokernot et al 1961 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…sudanensis and Ao. furfurea also supports existing evidence that it is maintained in nature by transovarial transmission ( Lutomiah et al 2014b ). NDUV was first isolated in South Africa in 1959, and antibodies to the virus have been detected in humans ( Kokernot et al 1961 ).…”
Section: Discussionsupporting
confidence: 82%
“…pipiens , and Mn. uniformis ( Crabtree et al 2009 , Ochieng et al 2013 , Lutomiah et al 2014a , Lutomiah et al 2014b ). Therefore, isolation of this virus from Ao.…”
Section: Discussionmentioning
confidence: 99%
“…Kenya harbors more than 80 different Aedes species () but not all have been associated with the spread of mosquito viruses. An important species is A. ochraceus which is highly distributed in the arid regions of north-eastern Kenya and linked to the spread of Rift Valley fever virus (RVFV), NDUV, Bunyamwera virus (BUNV), Babanki virus (BBKV), Sindbis virus (SNBV), and Semliki Forest virus (SMFV) in the region [4,11,34,35,36,37,38]. Additionally, this species has also been reported to be associated with RVFV, dengue virus (DENV), and chikungunya virus (CHKV) in coastal counties (Kwale, Kilifi, Mombasa, Lamu) [11,33,39], and some parts of in the western region [22].…”
Section: Overview Of the Main Mosquito Genera Of Public Health Impmentioning
confidence: 99%
“…Other alphaviruses have shown evidence of viable vertical transmission in mosquitoes and other insects. Examples of these include: western equine encephalitis virus, isolated from adult Aedes dorsalis collected as larvae 23 ; Ndumu virus, cultured from Culex pipiens grown from fieldcollected larvae 24 ; and Buggy Creek virus, isolated from eggs of Oeciacus vicarius swallow bugs. 25 On the basis of the findings of this and other studies, it should be concluded that detection of viral RNA itself is insufficient to confirm the occurrence of vertical transmission of CHIKV.…”
Section: Resultsmentioning
confidence: 99%